Mandible metastasis as the first sign from primary adenocarcinoma of the lung - Pereira-Filho, Valfrido Antonio [UNESP]; Chaves, Marcelo Donizetti; Haddad, Jorge; Gabrielli, Mário Francisco Real [UNESP]; Gabrielli, Marisa Aparecida Cabrini; Vieira, Eduardo Hochuli [UNESP]; Vargas, Pablo Agustin (My University, 2007)
Adenocarcinoma of the lung that metastasizes to the mandible is very uncommon; only a few cases have been described in the English-language literature. This article presents a metastasis from adenocarcinoma of the lung affecting the mandible of a 64-year-old woman, in which the first discovered metastatic lesion was detected before the primary tumor. The immunoreactivity for human thyroid transcription factor-1 (TTF-1) in the oral lesion was essential for determining the site and type of the primary tumor, as the patient showed no clinical or radiographic evidence of a tumor in the thyroid gland. After the primary tumor in the lung was diagnosed, radiotherapy and chemotherapy were initiated; unfortunately, the patient died two months after the start of treatment. This article emphasizes the importance of a well-conducted examination for diagnosing metastatic oral lesions.
Keywords: homeodomain protein; nuclear protein; thyroid nuclear factor 1; transcription factor; unclassified drug; adenocarcinoma; case report; fatality; female; human; lung tumor; mandible tumor; metastasis; middle aged; pathology; skull tumor; Adenocarcinoma; Fatal Outcome; Female; Homeodomain Proteins; Humans; Lung Neoplasms; Mandibular Neoplasms; Middle Aged; Nuclear Proteins; Skull Neoplasms; Transcription Factors